Formulation of Judges' Rulings Below the Special Minimum on Narcotics Cases to Bring About Justice - Andri Zulfikar (Journal of Social Research, 2023)
Narcotics crimes are classified as extraordinary crimes because these crimes are transnationally committed by a syndicate with the aim of destroying the nation in a conceptual and systematic way. The formulation of the problem in this writing is 1. How to consider the legal basis of judges below the specific minimum on narcotics cases to bring about justice. 2. How is the formulation of criminal charges below the specific minimum for narcotics cases to bring about justice? This research uses a normative juridical approach that emphasizes literature research. In this study, what is used is the Statutory approach, conceptual approach, case approach, historical approach, and philosophical approach. The type of legal material used is primary, secondary, and tertiary legal material the analysis used is to use qualitative descriptive analysis. The formulation of criminal penalties below the special minimum for narcotics cases to realize legal certainty in Article 112 paragraph (1) of Law No. 35 of 2009 against perpetrators of narcotics abuse will be sentenced to a maximum of 12 (twelve) years in prison and at least 4 (four) years, and with a maximum fine of Rp. 8,000,000,000.00 (eight billion rupiah). According to Article 191 paragraph (1) of the Criminal Procedure Code (KUHAP) has stated unequivocally that judges are not allowed to impose a sentence exceeding the maximum threat or under the minimum threat set forth in the article used by the public prosecutor in his indictment, if the charges charged against the defendant are not proven validly and convincingly then the defendant should be decided freely.